2019
DOI: 10.3389/fphar.2019.00652
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Cooling Compounds Icilin on Penicillin G-Induced Epileptiform Discharges in Anesthetized Rats

Abstract: More than 30% of patients with epilepsy are refractory and have inadequate seizure control. Focal cortical cooling (FCC) suppresses epileptiform discharges (EDs) in patients with refractory focal cortical epilepsy. However, little is known about the mechanism by which FCC inhibits seizures at 15°C, and FCC treatment is highly invasive. Therefore, new antiepileptic drugs are needed that produce the same effects as FCC but with different mechanisms of action. To address this need, we focused on transient recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…administered a single dose of PTZ (40 mg/kg). A model with focal epilepsy originating in the left cerebral cortex was generated by modifying a previously reported method (Moriyama et al, 2019).…”
Section: Drug-induced Epileptic Seizure Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…administered a single dose of PTZ (40 mg/kg). A model with focal epilepsy originating in the left cerebral cortex was generated by modifying a previously reported method (Moriyama et al, 2019).…”
Section: Drug-induced Epileptic Seizure Modelmentioning
confidence: 99%
“…ECoG was recorded by modifying a previously reported method (Moriyama et al, 2019). EDs developed 10-20 min after PG injection and reached a steady state 1.5 h after PG injection (Moriyama et al, 2019), remaining stable for at least 5 h (data not shown).…”
Section: Ecog Recordingmentioning
confidence: 99%
See 3 more Smart Citations